2021
DOI: 10.3897/bdj.9.e61848
|View full text |Cite
|
Sign up to set email alerts
|

An update to the distribution of invasive Ctenolepisma longicaudatum Escherich in northern Europe, with an overview of other records of Estonian synanthropic bristletails (Insecta: Zygentoma)

Abstract: Previously, two species of Zygentoma have been reported as synanthropic in Estonia (Lepisma saccharinum Linnaeus, 1758 and Thermobia domestica (Packard, 1873)). Ctenolepisma longicaudatum Escherich, 1905 is an invasive species that is currently expanding its range in Europe, but had no published records from the northern Baltic Region. Ctenolepisma longicaudatum was first found in Estonia in 2018. It has currently several established populations in public buildings in Tartu and Tallinn, but has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 699 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Rarely, the species can be found in steam tunnels, hot-water heaters and pipes or boiler rooms. According to Sammet et al (2021) the species was found in Estonia and it is also known form one museum in London (Val Blyth, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, the species can be found in steam tunnels, hot-water heaters and pipes or boiler rooms. According to Sammet et al (2021) the species was found in Estonia and it is also known form one museum in London (Val Blyth, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…The trapped silverfish was Ctenolepisma longicaudatum, and its distribution range is constantly expanding [29,30]. Silverfish have a vast food range, including grains rich in protein, sugar, trace elements, Chinese medicinal herbs, photos, paper, paste, cotton, animal fur, silk fibers, and even organic matter in indoor dust [31].…”
Section: Species and Distributionmentioning
confidence: 99%
“…Whether it is still widespread in Cuba today rema unknown, as with its occurrence and distribution in homes in Sri Lanka. In recent years, C. calvum has been recorded in different countries of Central Euro [3,6,[27][28][29][30][31][32]. The Integrated Pest Management (IPM) textbook by David Pinniger [6] d not include it as a pest species (although C. calvum was added in the German translat [33]).…”
Section: Introductionmentioning
confidence: 99%
“…The study provides an opportunity to assess likely changes in the fut and give a sense of issues that might require more consideration in pest management p tocols. In recent years, C. calvum has been recorded in different countries of Central Europe [3,6,[27][28][29][30][31][32]. The Integrated Pest Management (IPM) textbook by David Pinniger [6] does not include it as a pest species (although C. calvum was added in the German translation [33]).…”
Section: Introductionmentioning
confidence: 99%